Pengaruh Budaya Organisasi dan Motivasi Terhadap Kinerja Guru Madrasah - Nanang Kosim (Studia Manageria, 2020)
This study aims to uncover the influence of organizational culture and motivation on the performance of madrasa aliyah (MA) teachers throughout Tungkal Jaya District, Musi Banyuasin Regency (MUBA). The study was conducted with a quantitative approach with survey methods. The technique used to search and collect data, is to use an instrument in the form of a questionnaire. The existing population is 59 people, consisting of 32 people serving primarily as teaching staff and 27 people serving as primary teaching staff. Because this research is aimed at revealing the teacher's performance, the sample is those who have the main task as educators, and in this sample only 32 people are assigned. After the questionnaire was distributed and collected from 32 teachers (respondents), the results were then analyzed using the multiple linear regression formula with the help of SPSS version 11.5. The results of the analysis relate to the state of organizational culture, motivation and performance of teachers in the MA. all Tungkal Jaya Districts, Musi Banyuasin Regency, all three are in the quite good category with presentations of 66%, 69%, 66%. Then based on the outputs put out on the ANOVA table, the results of the f test show that organizational culture and motivationtogether have a significant effect on the performance of MA teachers throughout Tungkal Jaya District, MUBA Regency. This is based on the value F_calculate (28.082)> Ftable (3.32). Likewise, the value of sig (0,000) is smaller than the value of 0.05.